Next generation manufacturing in Singapore - Ker, Han Seah (2014)
The regional economic crisis and the more recent terrorist attacks have been watershed events for Singapore. Although Singapore emerged relatively unscathed from these upheavals, the economic challenges remain ever-daunting and furthermore, the playing field has been elevated from regionalization to globalization. Therefore, as part of the restructuring strategy, Singapore has identified manufacturing and services as the main engines for growth in the near future. However, by merely attracting manufacturers here to invest is no longer sufficient. It was realized that the much more value has to be added through upgrading the entire manufacturing sector by developing a new set of skills and capabilities, collectively known as Next Generation Manufacturing (NGM). Thus, the main aim of this report is to investigate how NGM can be applied to the Singapore context in preparation for tougher competition in the years to come.